2016
DOI: 10.1080/21505594.2016.1228508
|View full text |Cite
|
Sign up to set email alerts
|

Effect in virulence of switching conserved homologous capsular polysaccharide genes fromKlebsiella pneumoniaeserotype K1 into K20

Abstract: The capsular polysaccharides in different serotypes of Klebsiella pneumoniae (KP) coded by the (CPS) gene cluster are characterized by a conserved and a hyper-variable region. We performed a virulence study by switching genes in the highly conserved region of the CPS cluster between strains. Six genes in the CPS conserved region in serotype K20, including galF, acidPPc, wzi, wza, wzb and wzc, were knocked out and replaced by the homologous genes from serotype K1. Compared to the parental K20 strain, the mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…Conversely, switching the capsule serotype of the K21a strain to virulent K2 resulted in an increased virulence in mouse and in survival in blood and to a lower binding to macrophages [ 38 , 39 ]. In addition, switching highly conserved genes of the capsule cluster involved in capsule export from K1 into K20 hypervirulent strain strongly reduced its bacterial virulence in mice while increasing its neutrophil phagocytosis and survival in macrophages, although it is still not known whether this is due to a change in capsule expression[ 40 ]. However, a recent pan-genomic analysis did not reveal any correlation between capsule serotype and strains responsible of invasive community-acquired infection but rather suggested that the presence of one or several siderophores explains bacterial virulence [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, switching the capsule serotype of the K21a strain to virulent K2 resulted in an increased virulence in mouse and in survival in blood and to a lower binding to macrophages [ 38 , 39 ]. In addition, switching highly conserved genes of the capsule cluster involved in capsule export from K1 into K20 hypervirulent strain strongly reduced its bacterial virulence in mice while increasing its neutrophil phagocytosis and survival in macrophages, although it is still not known whether this is due to a change in capsule expression[ 40 ]. However, a recent pan-genomic analysis did not reveal any correlation between capsule serotype and strains responsible of invasive community-acquired infection but rather suggested that the presence of one or several siderophores explains bacterial virulence [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wza is responsible for transporting capsular polysaccharides from the periplasmic space to the surface of the bacterium, and it participates in the formation of bacterial capsules [21]. Homologues of Wza are found widely in Gram-negative bacteria, and Wza is reported to be a toxic factor in Escherichia coli [22], Klebsiella pneumoniae [23], Riemerella pestis [24], and Vibrio alginolyticus [25]. Other studies have reported the properties of Wza molecules in AB.…”
Section: Introductionmentioning
confidence: 99%
“…12 While deletion of galF and acidPPC genes, which are driven by the P1 promoter, 13 had limited effect on virulence, the deletion of genes driven by the P2 promoter (wzi, wza, wzb, and wzc) exhibited moderate to high effects on virulence. The deletion mutants of the latter genes, which are responsible for surface assembly, CPS polymerization, and CPS production, also showed high susceptibility to neutrophilic phagocytosis and to serum.…”
mentioning
confidence: 99%
“…In this issue of Virulence, Lin et al 12 describe the contribution of genes located in the highly conserved region of the cps locus to the virulence of K. pneumoniae. In this study, Lin et al identified a serotype K20 strain, which was isolated from a patient with a liver abscess, with high lethality in mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation